Homogeneity of the coronary microcirculation in angina with non-obstructive coronary artery disease - Hoshino, Masahiro; Hoek, Roel; Jukema, Ruurt A.; Dahdal, Jorge; van Diemen, Pepijn; Raijmakers, Pieter; Driessen, Roel; Twisk, Jos; Danad, Ibrahim; Kakuta, Tsunekazu; Knuuti, Juhani; Knaapen, Paul (Oxford University Press (OUP), 2025)
Aims
The homogeneity of coronary microvascular dysfunction (CMD) across different myocardial territories in angina with nonobstructive coronary artery disease (ANOCA) patients is scarcely explored. This study investigates the variability in microvascular resistance reserve (MRR) across the 3 main perfusion territories of the coronary circulation to investigate the homogeneity or dishomogeneity of microcirculatory function.
Methods and results
This post hoc analysis of the PACIFIC trials included symptomatic ANOCA patients with [15O]H2O positron emission tomography (PET) and three-vessel invasive fractional flow reserve (FFR). MRR was computed in the three main coronary branches by integrating PET-derived coronary flow reserve and invasive FFR. A total of 155 patients (50% male, age 59 ± 10 years) and 465 vessels (MRR: 3.92 ± 1.21) were included. There were no significant differences in MRR among the three coronary branches. Correlations in MRR among the three coronary branches were good (r = 0.76 to 0.86). The mean difference between MRR measurements in different arteries was small (2.4 to 7.5%), without any consistent directional bias. The overall intra-class correlation coefficient for absolute agreement was 0.80 (95% CI: 0.74–0.85), indicating good single-measure reliability. Approximately 80% (123/155) of patients showed diagnostic concordance of CMD (MRR ≤3.0) across the three vessels.
Conclusion
In most ANOCA patients, microvascular function is homogeneously distributed across the three major coronary territories. Single-artery testing may suffice in many cases, aligning with guidelines. However, some patients exhibit notable inter-territorial variation, suggesting that multi-vessel evaluation may be prudent in borderline scenarios.